Ex vivo Demonstration of Functional Deficiencies in Popliteal Lymphatic Vessels From TNF-Transgenic Mice With Inflammatory Arthritis - Scallan, Joshua P.; Bouta, Echoe M.; Rahimi, Homaira; Kenney, H. Mark; Ritchlin, Christopher T.; Davis, Michael J.; Schwarz, Edward M. (Frontiers in Physiology, 2021)
Background: Rheumatoid arthritis (RA) is a progressive immune-mediated inflammatory disease characterized by intermittent episodes of pain and inflammation in affected joints, or flares. Recent studies demonstrated lymphangiogenesis and expansion of draining lymph nodes during chronic inflammatory arthritis, and lymphatic dysfunction associated with collapse of draining lymph nodes in RA patients and TNF-transgenic (TNF-Tg) mice experiencing arthritic flare. As the intrinsic differences between lymphatic vessels afferent to healthy, expanding, and collapsed draining lymph nodes are unknown, we characterized the ex vivo behavior of popliteal lymphatic vessels (PLVs) from WT and TNF-Tg mice. We also interrogated the mechanisms of lymphatic dysfunction through inhibition of nitric oxide synthase (NOS). Methods: Popliteal lymph nodes (PLNs) in TNF-Tg mice were phenotyped as Expanding or Collapsed by in vivo ultrasound and age-matched to WT littermate controls. The PLVs were harvested and cannulated for ex vivo functional analysis over a relatively wide range of hydrostatic pressures (0.5 to 10 cmH2O) to quantify the end diastolic diameter (EDD), tone, amplitude (AMP), ejection fraction (EF), contraction frequency (FREQ) and fractional pump flow (FPF) with or without NOS inhibitors Data was analyzed using repeated measures two-way ANOVA with Bonferroni's post hoc test. Results: Real time videos of the cannulated PLVs demonstrated the predicted phenotypes of robust versus weak contractions of the WT versus TNF-Tg PLV, respectively. Quantitative analyses confirmed that TNF-Tg PLVs had significantly decreased AMP, EF and FPF versus WT (p<0.05). EF and FPF were recovered by NOS inhibition, while the reduction in AMP was NOS independent. No differences in EDD, tone, or FREQ were observed between WT and TNF-Tg PLVs, nor between Expanding versus Collapsed PLVs. Conclusion: These findings support the concept that chronic inflammatory arthritis leads to NOS dependent and independent draining lymphatic vessel dysfunction that exacerbates disease, and may trigger arthritic flare due to decreased egress of inflammatory cells and soluble factors from affected joints.